2015
DOI: 10.1093/jac/dkv185
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular typing of VRE bloodstream isolates in an Irish tertiary care hospital

Abstract: Irish VRE BSI isolates have virulence factor profiles as previously reported from Europe. Typing analysis shows the spread of individual clones within the hospital and between regional tertiary care hospitals. Apart from transmission of VRE within the hospital and transfer of colonized patients between Irish hospitals, no other explanation for the persistently high VREfm BSI rate in Ireland has been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…We further observed that the use of antibiotics of all classes predisposed both ACHand ITCF-admitted patients to VRE colonization. This is consistent with previous reports suggesting that antibiotic pressure selected for vancomycin resistance in enterococci (32)(33)(34). This also highlights the importance of good antimicrobial stewardship not only in ACHs but also in ITCFs for the prevention of VRE.…”
Section: Discussionsupporting
confidence: 92%
“…We further observed that the use of antibiotics of all classes predisposed both ACHand ITCF-admitted patients to VRE colonization. This is consistent with previous reports suggesting that antibiotic pressure selected for vancomycin resistance in enterococci (32)(33)(34). This also highlights the importance of good antimicrobial stewardship not only in ACHs but also in ITCFs for the prevention of VRE.…”
Section: Discussionsupporting
confidence: 92%
“…52 Only a few VRE fm strains (sequence type (ST)17, ST18, ST78, and ST203) cause invasive infections in blood or sterile body fluids according to the studies in Taiwan 53 and Ireland. 54 The nature of the classification problem would be more simple when the number of labels is fewer.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory infections could be the key source of XDR K. pneumoniae BSIs, which require a prolonged antibiotic therapy and are considered as an important factor for acquired resistance of pathogens (Ryan et al, 2015). The case-fatality rate attributed to BSIs caused by XDR K. pneumoniae here was 40% (14/35), the higher than the overall mortality rate (15–20%) associated with BSIs in previous studies (Russotto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%